Modeling Organizational Management in Institutions Learning EFL (English as Foreign Language): Approach Six Box Model - Hadisoebroto, Andreas Emmanuel; Sulindra, Eric (Educational Management, 2021)
Challenges for many institutional administrators EFL (English as Foreign Language) learning are building proper organizational management and the increasing number of educational institutions that manage EFL (English as Foreign Language) learning. This issue becomes significant, in line with the feedback from various surveys regarding the quality of language schools or educational institutions that assist EFL learning in related studies. These findings contribute to the design of EFL learning administration in any educational institution, especially in Southeast Asia. This study will map the pattern of administrative management applied in EFL educational institutions. The approach study is Descriptive qualitative. The locus of this research is three institutions at the Widya Mandala Foundation, Surabaya. Instrument collection of the data uses a questionnaire containing question-related variables in management organization , based on Six Box Models. Faculty of Teacher Training and Science Education: English Education Study Program, showing the best score in the Relationship Variable. The second institution is the Academy of Secretary Widya Mandala Surabaya. The result shows variable Attitude Towards Change has the best score. The third institution is the Widya Mandala Language Institute. This institution shows variable Purpose has the best score. Here _ seen that different EFL learning institutions evidently emphasize pattern management in other educational administrations. Finding this will be useful as consideration or suggestions for institution EFL learning in Case management organization, which aspects need to be noticed by intensive for smoothness organization.